Board Composition and Financial Performance: Empirical Analysis of Companies Listed at the Nairobi Securities Exchange - Vincent O. Ongore; Peter O. K'Obonyo; Martin Ogutu; Eric M. Bosire (International Journal of Economics and Financial Issues, 2014)
Studies investigating effects of board composition on financial performance have yielded mixed results, due largely to contextual variables and varying roles of boards in different jurisdictions. Independent members, gender diversity and board size are some of the key attributes of boards that have been linked to financial performance of companies in industrialized countries, but which, unfortunately have not attracted much scholarly interest in developing countries. The study, which surveyed forty-six companies listed at the Nairobi Securities Exchange in 2011, and whose findings are presented in this paper, was therefore, designed to inform practice of corporate governance mainly in developing countries, but will also add to the already existing body of literature in the industrialized economies. Using multivariate regression analysis on panel data, with Return on Assets, Return on Equity, and Dividend Yield as performance indicators, the study found out that independent board members had insignificant effect on financial performance, but gender diversity did, in fact, have significant positive effect on financial performance. Board size, on the other hand, had an inverse relationship with financial performance. These results are largely consistent with conceptual and empirical literature on corporate governance with respect to small board size (5 to 7) that is sufficiently diverse in terms of gender, skill, experience, industry networks, among other important attributes. Regarding outside directors, however, the study findings appear to contradict the long-held traditional view that outsiders confer superior performance to the board.